The Drosophila pericentrin-like protein is essential for cilia/flagella function, but appears to be dispensable for mitosis. - Martinez-Campos, M.; Basto, R.; Baker, J.; Kernan, M.; Raff, J.W. (Journal of Cell Biology, 2004)
Centrosomes consist of a pair of centrioles surrounded by an amorphous pericentriolar material (PCM). Proteins that contain a Pericentrin/AKAP450 centrosomal targeting (PACT) domain have been implicated in recruiting several proteins to the PCM. We show that the only PACT domain protein in Drosophila (the Drosophila pericentrin-like protein [D-PLP]) is associated with both the centrioles and the PCM, and is essential for the efficient centrosomal recruitment of all six PCM components that we tested. Surprisingly, however, all six PCM components are eventually recruited to centrosomes during mitosis in d-plp mutant cells, and mitosis is not dramatically perturbed. Although viable, d-plp mutant flies are severely uncoordinated, a phenotype usually associated with defects in mechanosensory neuron function. We show that the sensory cilia of these neurons are malformed and the neurons are nonfunctional in d-plp mutants. Moreover, the flagella in mutant sperm are nonmotile. Thus, D-PLP is essential for the formation of functional cilia and flagella in flies.